Factors Associated with Safe Motherhood Practices among Young Married Women - Karki, Rita Devi (Tribhuvan University Journal, 2021)
Safe motherhood is one of the key components of reproductive health and young women are notably concerned with the population of it in Nepal. This study attempts to analyze the factors associated with safe motherhood practices among young married women in five child marriage prevalence districts identified by UNFPA. The analysis uses data from research entitled “Situation Assessment of Child Marriage in Selected Five Intervention Districts of Nepal” conducted in 2017.It was confined to the women (N=239) who had at least one child. Bivariate analysis is used to identify the level of association between background characteristics and safe motherhood practices. The result showed nearly four in five (77.8%) women were married age at 15-19 years and more than three-fifth (61.1%) started to give birth. Regarding education, only 18 percent received the degree of SLC and above. Women who were engaged in marriage at below 15 have significantly fewer visits to the ANC in comparison to the women married at age 20-24 years. Women who have two or more children were significantly less likely to visit health institutions for delivery and PNC. The result indicates that adolescents face a high risk of complications during pregnancy and childbirth due to biological immaturity and socio-economic factors.